A bibliometric review on development economics research in Vietnam from 2008 to 2020 - Ho, Manh Toan (Springer, 2022)
This study adopts the bibliometric approach to identify the key characteristics in the relationship of demographic factors (age, gender, affiliations, and locations), scientific productivity, and the collaboration among development economics researchers in Vietnam during the period 2008–2020. Overall, the number of publications and authors in development economics are rising steeply with the average annual growth rate of nearly 23% and 26%, respectively. Moreover, the ‘quality’ of the research appears to be high as 59% of the articles are published in journals in the first and second quartile according Scimago journal ranking. However, the citation counts for these studies indicate their impacts are far more languishing in comparison. In terms of research trends, this study identified three emerging areas of studies that are relatively under-researched, namely natural resources, technology, and urbanization. As for publishing practices, There is also a positive sign for the adoption of open science among Vietnamese researchers in this field.